PERAN ORANG TUA DALAM MENDIDIK ANAK DITINJAU DARI HUKUM ISLAM - Darmawansyah, Darmawansyah (Pusat Studi Gender dan Anak, IAIN Palu, 2019)
The formation of personality is very meaningful, parents as the first personal coach in a child's life. Parenting activities are not only how parents treat children, but how parents educate, guide and protect children from childhood to adulthood in accordance with the values, norms and culture of the community. Parenting children in Islamic law (hadhanah) is the responsibility of both parents who should get special attention as; take care of, care for, educate and raise children who are still small and cannot take care of themselves, also parents should supervise children who are aged 7-18 years (adolescents) or the period after mumayyiz of things that are prohibited by Shari'ah, other than that in carrying out the duties of his hadhanah every parent must always be guided by Islamic rules based on the Qur'an and Al-Hadith.